Design and Comparative Study Among Antennas of GCS for Telemetry Communication System of UAV - Iswandi Iswandi; Aria Rangga Suryamanggala; Dewanto Wicaksono; Eny Sukani Rahayu (IJITEE (International Journal of Information Technology and Electrical Engineering), 2020)
Recently, Unmanned Aerial Vehicle (UAV) becomes a popular and interesting technology for researchers and academics because it has high potential to be implemented in various fields. The UAV operation is managed by a Ground Control Station (GCS) on which requires a communication system to send control signals and acquire data collected by sensors on UAV. The longer the UAV's flying distance needs a higher transmission power budget that can be achieved by increasing transmitter power, increasing receiver sensitivity, or increasing antenna gain. However, the design of communications systems on a flying platform is limited by the following constraints. The transmitter, receiver, and antenna must be compact, lightweight, and energy-efficient to save battery on the vehicle. Although the antenna does not directly influence the energy consumption from the battery, an increase in antenna gain usually requires an increase of the antenna dimension that causes higher weight and or reduces the aerodynamics. Therefore, the most efficient way to increase the link budget is by modifying the antenna on the GCS. This paper describes the analysis of antennas commonly used in GCSs for UAV communication links, namely the Yagi-Uda, bi-quad, and double bi-quad antennas. The antenna is designed to work at a frequency of 433.5 MHz following the transceiver device used. The antenna designs are numerically simulated then fabricated for evaluating their performance. The testing is done on the following issues, i.e. the antenna's basic parameters measurement, the ground-to-ground transmission test, and the ground to air transmission test. The test results show that the double bi-quad gives better performance than the other two other testing antennas.